Biomedical Application Prospects of Gadolinium Oxide Nanoparticles for Regenerative Medicine - Ekaterina V. Silina; Natalia E. Manturova; Elena L. Chuvilina; Akhmedali A. Gasanov; Olga I. Andreeva; Maksim A. Pugachevskii; Aleksey V. Kochura; Alexey A. Kryukov; Yulia G. Suzdaltseva; Victor A. Stupin (Pharmaceutics)
Background/Objectives: The aim was to study the possibilities of biomedical application of gadolinium oxide nanoparticles (Gd2O3 NPs) synthesized under industrial conditions, and evaluate their physicochemical properties, redox activity, biological activity, and safety using different human cell lines. Methods: The powder of Gd2O3 NPs was obtained by a process of thermal decomposition of gadolinium carbonate precipitated from nitrate solution, and was studied using transmission electron microscopy (TEM), X-ray diffraction (XRD), Raman spectroscopy, mass spectrometry, and scanning electron microscopy (SEM) with energy dispersive X-ray analyzer (EDX). The redox activity of different concentrations of Gd2O3 NPs was studied by the optical spectroscopy (OS) method in the photochemical degradation process of methylene blue dye upon irradiation with an optical source. Biological activity was studied on different human cell lines (keratinocytes, fibroblasts, mesenchymal stem cells (MSCs)) with evaluation of the effect of a wide range of Gd2O3 NP concentrations on metabolic and proliferative cellular activity (MTT test, direct cell counting, dead cell assessment, and visual assessment of cytoarchitectonics). The test of migration activity assessment on a model wound was performed on MSC culture. Results: According to TEM data, the size of the NPs was in the range of 2–43 nm, with an average of 20 nm. XRD analysis revealed that the f Gd2O3 nanoparticles had a cubic structure (C-form) of Gd2O3 (<semantics>Ia<mover accent="true">3)¯</mover></semantics> with lattice parameter a = 10.79(9) Å. Raman spectroscopy showed that the f Gd2O3 nanoparticles had a high degree of crystallinity. By investigating the photooxidative degradation of methylene blue dye in the presence of f Gd2O3 NPs under red light irradiation, it was found that f Gd2O3 nanoparticles showed weak antioxidant activity, which depended on the particle content in the solution. At a concentration of 10−3 M, the highest antioxidant activity of f Gd2O3 nanoparticles was observed when the reaction rate constant of dye photodegradation decreased by 5.5% to 9.4 × 10−3 min−1. When the concentration of f Gd2O3 NPs in solution was increased to 10−2 M upon irradiation with a red light source, their antioxidant activity changed to pro-oxidant activity, accompanied by a 15% increase in the reaction rate of methylene blue degradation. Studies on cell lines showed a high level of safety and regenerative potential of Gd2O3 NPs, which stimulated fibroblast metabolism at a concentration of 10−3 M (27% enhancement), stimulated keratinocyte metabolism at concentrations of 10−3 M–10−5 M, and enhanced keratinocyte proliferation by an average of 35% at concentrations of 10−4 M. Furthermore, it accelerated the migration of MSCs, enhancing their proliferation, and promoting the healing of the model wound. Conclusions: The results of the study demonstrated the safety and regenerative potential of redox-active Gd2O3 NPs towards different cell lines. This may be the basis for further research to develop nanomaterials based on Gd2O3 NPs for skin wound healing and in regenerative medicine generally.